20-HETE/GPR75 pairing modulates the expression and transcriptional activity of the androgen receptor in androgen-sensitive prostate cancer cells. (1st January 2023) - Cárdenas, Sofia; Colombero, Cecilia; Cruz, Mariana; Mormandi, Eduardo; Adebesin, Adeniyi Michael; Falck, John R.; Nowicki, Susana
Abstract: The androgen receptor (AR) and AR-driven genes are crucial in normal and neoplastic prostate tissue. Previous results showed a link between 20-hydroxyeicosatetraenoic acid (20-HETE) production and AR-driven prostate cancer (PCa) progression. This study aims to describe the contribution of GPR75, 20-HETE membrane receptor, in 20-HETE-mediated expression and transcriptional activity of AR in PCa. In LNCaP cells, 20-HETE increased AR expression, nuclear localization, and its transcriptional activity. Also, 20-HETE enhanced dihydrotestosterone (DHT) induced effects. All was abrogated by chemical antagonism of GPR75 (19-HEDE) or its transient knockdown. In human PCa, the expression of AR-driven genes correlated with GPR75. In LNCaP xenografts, tumors from castrated animals expressed higher levels of AR, this was impaired by inhibition of 20-HETE synthesis. These data suggest that 20-HETE, through the GPR75 receptor, regulates transcriptionally active AR in PCa cells, thus making 20-HETE/GRP75 potential targets to limit the expression of AR-driven phenotype in PCa cells. Graphical abstract: Image 1 Highlights: 20-HETE/GPR75 induces nuclear localization of the androgen receptor in LNCaP cells. It also increases the androgen receptor (AR) expression and transcriptional activity. Inhibition of 20-HETE synthesis prevents castration-induced tumor AR overexpression. Thus, 20-HETE/GPR75 regulates the availability of a transcriptionally active AR.